THE COMMUNITY SECTORS IN THE PRESERVATION OF PEACE AND ORDER - HABIATAN, ERIC N. (International Journal of Psychosocial Rehabilitation, 2020)
This study examined the community sectors in the preservation of peace and order in the municipality of Cabagan, Isabela, Philippines. Specifically, the extent of participation of the community sectors in the maintenance of peace and order and the functionality level of the community sectors in the preservation of peace and order were investigated. A total of 234 community sectors served as the respondents in this study. Descriptive design was used to analyze and interpret the data. Moreover, the needed facts were gathered through a validated and tested questionnaire. Findings showed the community sectors have moderate participation in the preservation of peace and order. The result indicated that significant differences exist between the extents of participation of the various sectors of the community. Further, the data stipulated that the community sectors are “moderately functioning” towards the maintenance of peace and order. There are also significant differences between the assessments of the various sectors on their functionality level. These figures imply that the various sectors in the community are cooperative in the preservation of peace and order wherein different sectors of the community are potential mechanism of public safety.